Efektivitas Kombinasi Dual Antipsikotik (Risperidone dan Olanzapine) serta SSRI dalam Manajemen Gangguan Skizoafektif Tipe Depresif : Laporan Kasus - Wynne Pratiwi; Juniar Effendi; Anastasia Ratnawati Biromo (KOLONI, 2026)
Schizoaffective disorder, depressive type, is a psychiatric condition characterized by the presence of psychotic symptoms within the context of mood episodes, particularly major depressive episodes. Clinical manifestations commonly involve hallucinations, delusions, and depressive symptoms such as low mood, reduced interest, sleep disturbance, decreased appetite, and suicidal ideation. The variability of presentation and the overlap between psychotic and affective symptoms may complicate both diagnostic assessment and therapeutic decision-making. This disorder is associated with significant functional impairment and an increased risk of suicide. We report a 22-year-old female who presented to the emergency department of a hospital in Jakarta with irritability, shouting, and aggressive speech, accompanied by auditory hallucinations described as whispering voices and visual hallucinations involving the image of her mother. Symptoms had been present for two months prior to admission and were associated with sleep disturbance, decreased appetite, weight loss, and suicidal ideation. Mental status examination revealed hypotymic mood, restricted affect, nonspontaneous speech, and the presence of both auditory and visual hallucinations. The patient was diagnosed with schizoaffective disorder, depressive type (F25.1). The patient was treated with a combination of risperidone, olanzapine, and sertraline to address both psychotic and depressive symptoms simultaneously. Although this approach is not considered first-line treatment in most clinical guidelines, it may be considered in selected cases with severe symptomatology and elevated suicide risk. The observed clinical improvement highlights the importance of individualized treatment planning, careful benefit–risk evaluation, and close monitoring of treatment response and tolerability.